The Feagaiga and Faife’au ‘Kids’ (FKs): An Examination of the Experiences of Parsonage Children of the Samoan Congregational Denomination in New Zealand - Muaiava, Sadat Petelo (2017)
This article examines the experiences of faife’au ‘kids’ (clergy children) of the Samoan Congregational Christian Church denomination in New Zealand. The paper investigates the effects the indigenous concept of feagaiga (covenant) has on faife’au kids (FKs) parsonage experiences. Additionally, the Eurocentric concept of ‘tagata’ese’ (stranger) is also investigated. As part of a master’s research study, Talanoa sessions were conducted with eight FKs of the Congregational denomination in New Zealand. Participants were mainly from the Wellington and Auckland regions.
Keywords: Samoan youth; feagaiga; faife’au kids; Faife'au